Remineralization of Incipient Lesions with Anticariogenic Casein Phosphopeptides and Fluoride: A Vivo Study - Khanduja, Ritu; Verma, Rupanjali; Tandon, Shobha (Journal of Pierre Fauchard Academy (India Section), 2019)
Objective: The aim of this study was to evaluate the remineralization of incipient lesions with CPP-ACP and its comparison with the effect of fluoride on the same. Study Design: A total of 225 teeth with incipient lesions in 108 children within the age group of 6-14 yrs. were divided into five groups by block randomization. Enamel biopsy was done for incipient lesions. Calcium and phosphate were analyzed using auto analyzer, fluoride was assessed using Orion analyzer. Results: Results showed that CPP-ACP enhances the remineralization process and that CPP-ACP has comparable effect as fluoridated dentifrice, as difference was not statistically significant (p>0.05), using ANOVA, Tukey’s test. Conclusion: CPP-ACP is effective remineralizing agent. A beneficial dose response effect is seen with the application of casein phosphopeptides. In addition, there is a synergistic effect of CPP-ACP with fluoride.